2023
DOI: 10.3390/f14040829
|View full text |Cite
|
Sign up to set email alerts
|

Seed Harvesting and Climate Change Interact to Affect the Natural Regeneration of Pinus koraiensis

Abstract: The poor natural regeneration of Pinus koraiensis is a key limitation for restoring the primary mixed Pinus koraiensis forests. Seed harvesting and climate change are the important factors that influence the natural regeneration of Pinus koraiensis; however, it is hard to illustrate how, in synergy, they affect its regeneration at the landscape scale. In this study, we coupled an ecosystem process model, LINKAGES, with a forest landscape model, LANDIS PRO, to evaluate how seed harvesting and climate change inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Their results indicated a reduction in highly suitable areas under future climate conditions and acknowledged the importance of identifying viable habitats to conserve vulnerable species and prevent local extinctions. Other papers published in this Special Issue have shown that climate changes affect vegetation phenology [12], tree growth [13] and stand productivity [14] but also the reproductivity rate [15] or stand regeneration [16]. Using remote sensing data, such as MODIS together with vegetation indices and vegetation gross primary productivity [12,14], allows the identification of changes in vegetation changes and the link to climate change.…”
Section: Summary Of Main Outputs and Findingsmentioning
confidence: 99%
“…Their results indicated a reduction in highly suitable areas under future climate conditions and acknowledged the importance of identifying viable habitats to conserve vulnerable species and prevent local extinctions. Other papers published in this Special Issue have shown that climate changes affect vegetation phenology [12], tree growth [13] and stand productivity [14] but also the reproductivity rate [15] or stand regeneration [16]. Using remote sensing data, such as MODIS together with vegetation indices and vegetation gross primary productivity [12,14], allows the identification of changes in vegetation changes and the link to climate change.…”
Section: Summary Of Main Outputs and Findingsmentioning
confidence: 99%
“…In addition, the migration ability of P. koraiensis is limited due to its phenotypic plasticity, seed dispersal ability, reproductive capacity, and degree of range fragmentation, making it unable to occupy new ecological niches, resulting in a serious decline in these population. Consequently, the populations in these isolated patches are difficult to recover through natural regeneration (Liang et al, 2018;Liu et al, 2023). In addition, climate-induced changes in the location of suitable habitats may cause the distribution of P. koraiensis to deviate from existing protected areas, and the reduction in the P. koraiensis population caused by human destruction in nonprotected areas must also be carefully considered (Araújo et al, 2004;Heller and Zavaleta, 2009).…”
Section: Introductionmentioning
confidence: 99%